NAME CHANGE IN THE JAVANESE CULTURAL SYSTEM IN SERAT TATA CARA NIPUN TIYANG NGLUWARI PUNAGI - Hari Pamungkas; I Made Suparta (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This paper discusses the text of Serat Tatacaranipun Tiyang Ngluwari Punagi PBC 17 collection of Library Museum Sonobudoyo Yogyakarta. Mambahas customary law practice in villages in Karaton Surakarta. This study aims to reveal the mystical side of the text of Fiber Tatacaranipun Tiyang Ngluwari Punagi. This manuscript tells Rara Suparti who later renamed RadenRaraSuparmi for being sicks. This research uses interpretative and qualitative method with shortlist objective. The theoretical benefit of this research is to become an information booster for further studies. The practical benefit of this research is in the form of knowledge for the general public to know the mystical events of renaming the Javanese environment. The name renaming is one of the mystical events in the Java environment of the manuscript Serat Tatacaranipun Tiyang Ngluwari Punagi.